THE EXISTENCE OF WOMEN ON THE MURDERER IN FOUR STAG-ES BY MOULY SURYA - Harmita Sari; Anita Hafid; Kartini Kartini; Sukmawati Tono Palangngan; A. Nurhayati (Universitas Negeri Makassar, 2021)
This study aims to describe: (1) the treatment of women and (2) the causes of oppression of women, based on the multicultural feminism perspective. This study is qualitative. The data in this study are in the form of text and images of contextual elements containing the existence of women in the form of treatment and causes of oppression of women in the Marlina the Murderer in Four Acts movie. The data was collected through three techniques, namely: documentation technique, listening technique, and transcript technique, and to add the valid data, the researchers used the N-Vivo application by retrieving data from online media, namely news republika, compass, tempo, detik.com, news that discusses the Marlina film. The data results are in the form of images, tables and diagrams, then described by researchers, supported by relevant theories. Then, the data was analyzed by using feminism theory by Simon De Beauvoir and multicultural feminism theory by Audre Lorde. The analysis was done through three phase namely indentification, classification, and data presention. The results of this study indicate: (1) the treatment of women is divided into two, namely: the characteristics of woman feminine and the types of women. The characteristics of women consist of: fear, weakness, patience, kindness, submission, inferiority, alertness, anxiety, hope and imagination. While, the types of women are narcissistic, prostitute, and mystical women. (2) The causes of women's oppression are sexism, racism, classism and ethnicity.